SUSTAINABLE DEVELOPMENT CONCEPT AWARENESS AMONG STUDENTS IN HIGHER EDUCATION : PRELIMINARY STUDY - Florianna Lendai, Michael Mulok; Sumilan, Helmi; Nur Fatihah, Abdullah Bandar; Hana, Hamidi; Jonathan, Victoria; Nik Norsyamimi, Md Nor (Universiti Malaysia Terengganu, 2020)
As higher education is given a primary role as knowledge producers; it serves as a powerful means to help create a more sustainable future which involves educating students on the necessity of sustainable development. The purpose of this case study was to survey the students’ awareness, attitudes and actions in regard to sustainable development. The study was conducted in one of the public universities in Malaysia located in Kota Samarahan. Questionnaire was developed based on learning objectives provided by UNESCO and data were analysed using ANOVA test. A total of 79.2% (N=507) of students from the same programme participated in the study. Results indicated that 40.7% (N=239) students have insufficient knowledge on sustainable development. Further findings revealed that the final year students have the highest level of sustainability awareness (M=3.918, SD=.517), attitudes (M=4.349, SD=.514) and actions (M=4.365, SD=.538) as compared to Year 1 and 2. In the efforts towards supporting sustainability education evolution, universities need to embed the sustainability aspects into their mission, vision, objectives and the philosophy in the management structure which include the considerations of formal committee, roles and responsibilities, assessment framework for performance.